METHOD OF ACOUSTIC PRESSURE ESTIMATION GENERATED BY THE AVIATION GAS-TURBINE ENGINE FAN - Терещенко, Ю.; Дорошенко, К. (Science-based technologies, 2010)
Method of acoustic pressure estimation generated by the aviation gas-turbine engine fan, taking into account values of fan’s efficiency, were developed. A method is based on the numeral experiment.